MTMR6 downregulation contributes to cisplatin resistance in oral squamous cell carcinoma - Kah Young Lee; Su Young Oh; Heon-Jin Lee; Tae-Geon Kwon; Jin-Wook Kim; Chang-Geol Shin; Su-Hyung Hong; So-Young Choi (Cancer Cell International)
Abstract Background The therapeutic effectiveness of cisplatin, a widely used chemotherapy drug for oral squamous cell carcinoma (OSCC), is often compromised by resistance, making it difficult to predict treatment outcomes. The role of myotubularin and myotubularin-related (MTMR) genes in cisplatin resistance remains unclear. We aimed to elucidate the molecular mechanisms underlying MTMR6 with cisplatin resistance in OSCC. Methods MTMR6 expression was compared between UMSCC1 and cisplatin-resistant UM-Cis cells. Gain- and loss-of-function experiments involving MTMR6 was performed to evaluate its impact on cisplatin resistance. The regulatory role of hsa-miR-544a on MTMR6 expression was explored via antagomir and miRNA mimic assays. The relationship between MTMR6 protein levels and cisplatin sensitivity was assessed in OSCC patient tissues classified as sensitive or resistant to cisplatin monotherapy. A survival analysis based on The Cancer Genome Atlas (TCGA) head and neck squamous cell carcinoma (HNSCC) dataset was performed to evaluate the correlation between MTMR6 expression and patient outcomes following cisplatin treatment. In vivo cisplatin resistance was examined using mouse xenografts derived from MTMR6-knockdown UMSCC1 cells. Results MTMR6 expression was markedly reduced in cisplatin-resistant UM-Cis cells compared to UMSCC1 cells. Functional analyses revealed that modulating MTMR6 activity alters cisplatin resistance. A luciferase assay confirmed that hsa-miR-544a regulates MTMR6 gene expression. Additionally, antagomir and miRNA mimics demonstrated that hsa-miR-544a enhances cisplatin resistance by suppressing MTMR6 expression. In OSCC patient tissues, higher MTMR6 protein levels were associated with cisplatin sensitivity, while cisplatin-resistant tissues had lower MTMR6 expression. Survival analysis of the TCGA HNSCC dataset indicated that low MTMR6 expression correlates with poorer outcomes in cisplatin-treated patients compared to those with high MTMR6 expression. Mouse xenografts derived from MTMR6-knockdown UMSCC1 cells exhibited increased resistance to cisplatin compared to controls. Conclusion Assessing mRNA levels of MTMR6 and has-miR-544a in biopsy samples could help predict cisplatin responsiveness in OSCC.